Dental caries in a Portuguese identified skeletal sample from the late 19th and early 20th centuries - Wasterlain, Sofia N. (2009)
Dental caries was investigated in 600 adult dentitions belonging to the identified osteological collections of the Museum of Anthropology, University of Coimbra, Portugal (late 19th/early 20th centuries). The main advantage of this sample compared to an archaeological source is the presence of known demographic parameters such as age, sex, and occupation. The aim of this study is to investigate the issues involved in comparing caries data derived from archaeological death assemblages with statistics compiled from clinical studies of the living. When only the upper dentition was considered, higher rates were observed in females than in males. No differences were found between sexes for lower teeth. In both sexes, both the percentage of carious teeth and the severity of lesions were found to increase with age, demonstrating that caries activity continued throughout life. The slight decrease observed for the age group 70-79 years is probably due to the increased antemortem tooth loss in the elderly. Caries was most common at contact areas (32.9%) and rarest at smooth crown surfaces (6.5%). Root surface caries was graphed in relation to the exposure of roots, and it was confirmed that the degree of root exposure was not strongly related to the frequency of carious lesions on the exposed root surface, although both increased with age. Molars were attacked more frequently by caries as a whole than premolars, canines or incisors. The results are similar to studies of recent living populations with a limited access to professional dental care.